A CMOS Image Sensor with Analog Pre-Processing Capability Suitable for Smart Camera Applications - Söll, Christopher; Shi, Lan; Bänisch, Andreas; Ußmüller, Thomas; Weigel, Robert (IEEE International Symposium on Intelligent Signal Processing and Communication Systems (ISPACS), 2015)
This work presents a novel CMOS sensor which is suitable for analog image processing operations and describes the benefits of analog pre-processing over digital algorithms. All needed modifications to read out a spatial NxN pixel matrix simultaneously are presented regarding pixel wiring, row decoder and column multiplexer as well as descrambling the order of the outputs. The outputs are connected via a buffer stage to the analog pre-processing circuits. As an example for such an analog computation, an averaging filter is described from design constraints to the actual implementation. Simulation results show a very low current consumption of just 55.3 μA under worst-case conditions and a computation time below 200 ns. This corresponds to a power-time product ratio of 1:18.75 compared to a digital state-of-the-art implementation.
elib2cris::1512001600,soell2015b
Keywords: Smart Cameras; CMOS Image Sensors; Analog Processing Circuits; Filtering Algorithms; GRK-1773

A flexible mixed-signal image processing pipeline using 3D chip stacks - Shi, Lan; Söll, Christopher; Pfundt, Benjamin; Bänisch, Andreas; Reichenbach, Marc; Seiler, Jürgen; Ussmueller, Thomas; Weigel, Robert (Journal of Real-Time Image Processing, 2016)
This work presents a highly flexible mixed-signal CMOS image sensor suitable for smart camera applications. These systems need to fit different constraints regarding power consumption, speed and quality, and the optimal compromise may differ depending on the application. Moreover, the best implementation of a desired image processing task may be in the analog or the digital domain, or even a combined computation. Different aspects starting from the image sensor and signal acquisition up to the pre-processing in analog and digital domain are investigated in this paper to optimize not just one part of the system, but the whole system altogether. Moreover, it is shown that analog processing algorithms can improve signal quality, processing speed and latency while being able to save power, which is important for real-time systems. In order to be able to carry out spatial operations, the state-of-the-art sensor is modified to be able to read out multiple pixels at the same time. This allows analog spatial filter operations which consume significantly less power. As an example, an averaging filter is described which needs less than 5.3 % of the power–time product of a digital implementation for one computation. To enhance data throughput and flexibility, 3D chip stacking is proposed to partition the sensor in smaller units and enable massively parallel processin
Keywords: 3D chip stacking; Analog pre-processing; Application optimized image pipeline; Partitioning; Smart camera

A Multi-Functional Reconfigurable Low-Power Ultra-High PSRR CMOS Reference-System - Söll, Christopher; Bänisch, Andreas; Röber, Jürgen; Shi, Lan; Weigel, Robert (IEEE Conference on PhD Research in Microelectronics and Electronics (PRIME), 2015)
This paper presents a new reference system with emphasis on low power design and high power supply rejection. The untrimmed reference provides a 600mV output voltage, which only differs by 5.75mV in the temperature range between -40 ◦ C and +125 ◦ C and a PSRR of -157.2 dB at 10Hz. The core part of the reference produces a reference potential of 416.1mV with a deviation of only 1.59mV. Moreover, the circuit provides a 900mV output, a temperature independent 3 μA current and trimming possibilities for the temperature curves and the amplitude of output voltages and currents. Under all operating conditions, the post-layout Corner- and Monte-Carlo-Simulations show a power consumption of less than 40 μA and ensure functionality across process, supply voltage and temperature variations.
elib2cris::1512001600,soell2015
Keywords: bandgap; reference; low power; high psrr; temperature coefficient; subregulation; GRK-1773

Analog Computation Methods with the help of analog and pseudo-digital Carry Signals - Söll, Christopher; Shi, Lan; Bänisch, Andreas; Röber, Jürgen; Ußmüller, Thomas; Weigel, Robert (IEEE European conference on circuit theory and design (ECCTD), 2015)
This work describes new methods of handling exceedings of the supply range in analog computation stages. These are handled as pseudo-digital and analog carry signals and used to regulate the gain of the stage where they occur as well as all computation stages that follow. A complete example for such an analog computation is simulated and presented and critical parts of the architectures are addressed. In addition, more sophisticated extensions are proposed and the ”right” way of carry handling is explained for a specific algorithm, together with a discussion of the advantages of different methods for each application.
elib2cris::1512001600,soell2015a
Keywords: analog computation; analog carry; pseudo-digital carry; pre-processing; GRK-1773

Analog Non-Linear Transformation-Based Tone Mapping for Image Enhancement in C-arm CT - Shi, Lan; Berger, Martin; Bier, Bastian; Söll, Christopher; Röber, Jürgen; Fahrig, Rebecca; Eskofier, Björn; Maier, Andreas; Maier, Jennifer (IEEE Medical Imaging Conference (MIC), 2016)
Flat-Panel C-arm Computed Tomography (CT) suffers from pixel saturation due to the detector’s limited dynamic range. We describe a novel approach to analog, non-linear tone mapping (TM) for preventing detector saturation. An analog TM operator (TMO) applies a non-linear transformation in a CMOS sensor and its inverse TMO based on 14-bit digital raw data. This is done in order to prevent overexposure and to enhance image quality to 32 bits. The method was applied to the cases of low-contrast head imaging and to that of imaging both knees. Cone-beam projection data with and without overexposure was simulated for a 200° short-scan of the knees and a 360° full-scan of a Forbild head phantom. The results show an increased correlation coefficient of 0.99 compared to 0.96 for overexposed knee data and a higher low-contrast visibility (CC=0.99) compared to linear quantization (CC=0.97
elib2cris::1512001600,shi2016a
Keywords: GRK-1773

A Tone Mapping Algorithm Suited for Analog-Signal Real-Time Image Processing - Shi, Lan; Hadlich, David; Söll, Christopher; Ußmüller, Thomas; Weigel, Robert (12th International Conference on PhD Research in Microelectronics and Electronics (PRIME), 2016)
This work presents a Tone Mapping Operator (TMO) which adjusts the High Dynamic Range (HDR) of image sensor data to the limited dynamic range of conventional displays with analog signal processing. It is based on Photographic Tone Reproduction (PTR) and suitable for analog circuit design in a CMOS image sensor in order to reduce the hardware cost and operation time for real-time image processing. For this reason, the characteristic advantage and calculation limitation of analog technology are considered in the TMO algorithm proposal. Furthermore, the appropriate modelling is built and simulated in Verilog-A. The function of the algorithm is feasible for analog processing. The frequency of the analog TMO is upper 52MHz while it consumes 55mW. The simulation results of test images are compared with the digital global TMO and the proposed analog TMO provides a reasonable similar dynamic range compression.
elib2cris::1512001600,shi2016
Keywords: Image Processing; Tone Mapping; CMOS Image Sensor; Analog Circuit; GRK 1773

Concept for a CMOS Image Sensor Suited for Analog Image Pre-Processing - Shi, Lan; Söll, Christopher; Bänisch, Andreas; Weigel, Robert; Seiler, Jürgen; Ußmüller, Thomas (DATE Friday Workshop on Heterogeneous Architectures and Design Methods for Embedded Image Systems, 2015)
A concept for a novel CMOS image sensor suited for analog image pre-processing is presented in this paper. As an example, an image restoration algorithm for reducing image noise is applied as image pre-processing in the analog domain. To supply low-latency data input for analog image preprocessing, the proposed concept for a CMOS image sensor offers a new sensor signal acquisition method in 2D. In comparison to image pre-processing in the digital domain, the proposed analog image pre-processing promises an improved image quality. Furthermore, the image noise at the stage of analog sensor signal acquisition can be used to select the most effective restoration algorithm applied to the analog circuit due to image processing prior to the A/D converte

Dynamic Pixel Binning allows Spatial and Angular Resolution Tradeoffs to improve Image Quality in X-Ray C-Arm CT - Steg, Alexander; Reichenbach, Marc; Söll, Christopher; Shi, Lan; Maier, Andreas; Riess, Christian (IEEE International Symposium on Biomedical Imaging (ISBI), 2016)
When designing an acquisition protocol for a C-arm CT acquisition, a tradeoff has to be made between scan time and the amount of acquired data. If the scan is increased, data of spatially and angular higher resolution can be acquired. If the scan time is fixed, one has to tradeoff spatial and angular resolution, which may either lead to oversmoothing or artifacts from angular undersampling. In this work, we investigate the viability of smart cameras for pushing the boundary for this bottleneck considerably further. The detector pixels are enhanced by processing units that are able to perform a limited amount of local operations. This allows an online, dynamical adaptation of the pixel binning, depending on whether a local neighborhood is smooth or not. We demonstrate on phantom data that this approach allows to save about 75% of the data, obtaining a reconstruction quality comparable to 1 x 1 binning at a data rate comparable to 2 x 2 pixel binning.
elib2cris::1512001600,steg2016
Keywords: Pixel Binning; X-ray detector; C-arm reconstruction; Dynamic Pixel Binning; X-ray C-arm CT

Low-Power Analog Smart Camera Sensor for Edge Detection - Söll, Christopher; Shi, Lan; Röber, Jürgen; Reichenbach, Marc; Weigel, Robert; Hagelauer, Amelie Marietta (IEEE International Conference on Image Processing (ICIP), 2016)
This work presents an intelligent analog image sensor system for smart camera applications with the need of edge or marker detection. The system consists of a 3x3 read-out CMOS image sensor, an analog Sobel stage and additional circuitry like operational amplifiers and comparators to compute a 1bit image with the edges present in the taken photo. This information can then be further processed digitally to detect specific shapes in order to control robot routines, for example. The architecture of the proposed system is highly desirable as dedicated analog hardware has significant advantages in terms of power and speed compared to digital implementations. The overall system is simulated with the help of a 3x3 CMOS image sensor IC as well as Cadence Virtuoso for analog circuit simulation and MATLAB to convert the sequential information back to an image, and compared to other state of the art CMOS image sensors with edge detection capability. The analog Sobel circuit runs with a clock of 10MHz and consumes less than 0.79mW average power for the computation of the example image, and the whole 200x200 pixel image sensor consumes only 5.5mW at a frame rate of 75 fps.
elib2cris::1512001600,soell2016
Keywords: Smart Camera; CMOS Image Sensor; Analog Processing Circuits; Analog Sobel; GRK-1773

Low-Power High-Gain Operational Amplifier for Analog Image Pre-Processing in Smart Sensor Systems - Söll, Christopher; Mai, Timo; Shi, Lan; Röber, Jürgen; Ußmüller, Thomas; Weigel, Robert; Hagelauer, Amelie Marietta (15. ITG/GMM-Fachtagung Analog 2016, 2016)
In this work, a low-power high-gain operational amplifier is presented, which is dedicated to work in an analog image pre-processing stage in a smart sensor system. This stage is able to detect edges and shapes for instance, before the image is passed to the ADC and the digital computation stage, reducing data and precision requirement of both stages. This approach helps to save power, making smart image sensor nodes with energy harvesting reasonable. Since the precision as well as the energy consumption of the edge detection algorithm is highly depended on the amplifier used for the basic summing and multiplier blocks, the design of it plays an important role for the approach. The proposed input/output rail-to-rail operational amplifier is based on a 150 nm CMOS process, has a gain of 77 dB and a unity gain bandwidth of 45.7MHz while consuming only 77 μA statically at a supply voltage of 1.8V.
elib2cris::1512001600,soell2016c
Keywords: analog pre-processing; operational amplifier; low-power; high-gain; folded-cascode; GRK-1773